E-058 An alternative reduced dose regimen of ticagrelor for neuroendovascular patients. (23rd July 2022) - Thind, S; Morsi, R; Kass-Hout, O; Stern, J; Tangonan, R; Kass-Hout, T; Guterman, L
Abstract : Introduction/Purpose: There is a growing use of ticagrelor in patients undergoing neuroendovascular procedures, especially those who demonstrate clopidogrel resistance. While multiple dosages are studied in the cardiology literature, the optimal dose for patients with neurological pathology has yet to be established. Here, we describe a single center experience involving 39 patients who underwent neuroendovascular procedures that then received an adjusted lower dose of ticagrelor. Materials and Methods: A retrospective chart review was performed between 2013 and 2017 for patients on dual antiplatelet therapy (DAPT) for either cervical or intracranial vascular pathologies, as well as stenting of the neurovasculature, including carotid arteries. Patients were placed on ticagrelor if their measured P2Y12 reaction units (PRU) responses to clopidogrel were outside the expected range in our center using the VerifyNow™ P2Y12 test. All patients were maintained on a dose of 45 mg twice daily except for one patient who received 22.5 mg twice daily. Responsiveness to ticagrelor were measured utilizing the VerifyNow™ P2Y12 test. Results: The mean number of days for follow up post treatment initiation was 532 days. A total of 39 patients were included in the analysis. Of these, 8 patients (21%) received implantation of intracranial stents (5 patients received pipeline embolization devices, 1 patient received stent- assisted coiling, and 2 patients received intra-cranial stents for atherosclerotic disease). Fourteen patients (35%) received carotid angioplasty and stenting. Seventeen patients (44%) did not receive permanent implantation of a stent. All patients on the lower dose Ticagrelor of 45 mg twice daily achieved responsiveness (i.e., PRU < 194). Hemorrhagic transformation of ischemic stroke occurred in one patient (2.5%). No other hemorrhagic complications were encountered. No thromboembolic events were recorded aside from one patient (2.5%) with intracranial atherosclerotic disease who had an ischemic event. Conclusion: A lower dose of ticagrelor (45 mg twice daily) appears to be a safe and effective in this small cohort of patients who are resistant to clopidogrel per P2Y12 testing and who have increased risk of ischemic or hemorrhagic strokes due to neurovascular pathologies and implants. Further randomized studies are required to confirm these findings. Disclosures: S. Thind: None. R. Morsi: None. O. Kass-Hout: None. J. Stern: None. R. Tangonan: None. T. Kass-Hout: None. L. Guterman: None.